Too many leprechauns, or, How that pot o' gold got to the end of the rainbow - Krensky, Stephen (Simon & Schuster Books for Young Readers, 2007)
Finn O'Finnegan returns home after a year in Dublin and when he finds his village taken over by leprechauns, he must devise a way to get them to leave without making them angry.